Main street evolved: envisioning a comprehensive approach to main street redevelopment in small mountain communities - Murner, Cory James (Kansas State University, 2011)
The main streets of the Rocky Mountain West are the social, economic, and cultural centers of their respective communities. Often, these main streets may deteriorate or become abandoned as a result of edge shopping malls and strip style economic development. Thus, a downtown or main street redevelopment effort by the community can help to ensure these economic centers remain. Yet, too often, the redevelopment efforts are oversimplified and fail to integrate the most current street development principles and design initiatives that can benefit not only the community but also the surrounding environment. I n the modern American city, almost half of all daily trips are less than three miles and a third are under one mile. (McCann 2010) “These are distances easily traversed by foot or bicycle, yet 65 percent of trips under one mile are made by automobile.” (McCann 2010) This mobility trend has led to the foundation of programs and organizations that try to promote non-motorized travel. Although these initiatives respond to the human/physical environment, they are far from comprehensive. Today, an integration of smart ecological ideals is essential. How can the revitalization efforts of Rocky Mountain communities be guided to ensure they consider not only the built environment; but also the natural environment? The face of the future main street will be multi-modal and ecologically responsible. Yet, there is presently no clear method of combining the two. A union of the multi-modal principles behind Complete Streets and the ecologically responsible ideals green infrastructure can provide a framework for a new and more inclusive redevelopment approach. The merging of modern ecological and street design principles can lead to a comprehensive Main Street redevelopment program and therefore successfully guide the revitalization efforts of small Rocky Mountain communities in a way that is responsive to future development needs as well as the cultural and ecological aspects of the region. Main Street Evolved will provide a set of tools to guide Colorado Rocky Mountain Main Street redevelopment efforts by providing strategies and implementation guidelines that focus on balancing multi-modal ideals and ecological stormwater management techniques within a small-town mountain context.
Keywords: Main Street; Multi-Modal; Green Infrastructure; Place Making; Rocky Mountain West; Landscape Architecture (0390); Land Use Planning (0536)